PENGARUH KUALITAS PELAYANAN DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN (Studi Kasus Pada Pengguna Jasa Transportasi BPU. Rosalia Indah) - Yulianingsih, Dian Kurnia; Hidayat, Wahyu; Budiatmo, Agung (Jurnal Ilmu Administrasi Bisnis, 2013)
This study aimed to to determine the effect variables of Quality of Service and Customer Satisfaction on Customer Loyalty Transportation Users BPU. Rosalia Indah. This type of research used is explanatory research, data collection methods using an oral interview and a data collection tool using a questionnaire with a sample of 100 respondents who use the services of the BPU. Rosalia Indah via nonprobability sampling technique by using purposive sampling method. The results of the statistical linear regression analysis can be shown by the regression equation Y = 3.296 + 0.136 X1 + 0.666 X2 e. From the regression equation it is known that the quality of service and customer satisfaction has an effect on customer loyalty. The results of the calculation of the coefficient of determination 0.468 magnitude. It is indicating that the quality of service and customer satisfaction variables could explain 46.8% of consumer loyalty. Based on the results of the data analysis we can conclude the existence effect of service quality and customer satisfaction to customer loyalty BPU Rosalia Indah users. and have a strong level of closeness relationship this means that the higher quality of service and customer satisfaction that will lead to the higher customer loyalty. Companies can improve the quality of care by increasing service ticketing and departure schedule more regularly in order to be more timely.